2019
DOI: 10.1111/jep.13230
|View full text |Cite
|
Sign up to set email alerts
|

Unconditional and conditional monetary incentives to increase response to mailed questionnaires: A randomized controlled study within a trial (SWAT)

Abstract: Rationale, aims, and objectives: High response rates to research questionnaires can help to ensure results are more representative of the population studied and provide increased statistical power, on which the study may have been predicated. Improving speed and quality of response can reduce costs. Method:We conducted a randomized study within a trial (SWAT) to assess questionnaire response rates, reminders sent, and data completeness with unconditional compared with conditional monetary incentives. Eligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Hardy et al found no evidence that an unconditional incentive of a £10 gift voucher increased response to a postal questionnaire at one year in a trial of a maternal intervention at child birth (12). In contrast Young et al found that overall an unconditional incentive of a £5 gift voucher in a lung cancer screening trial in adults aged 50 to 75 did increase response although the questionnaire return was very high (> 90%) in both groups at all time points (one, 3, 6 and 12 months) (13). Since this SWAT started more SWATs of unconditional versus conditional trials of monetary incentives for retention have started (14), which are yet to report.…”
Section: Discussionmentioning
confidence: 86%
“…Hardy et al found no evidence that an unconditional incentive of a £10 gift voucher increased response to a postal questionnaire at one year in a trial of a maternal intervention at child birth (12). In contrast Young et al found that overall an unconditional incentive of a £5 gift voucher in a lung cancer screening trial in adults aged 50 to 75 did increase response although the questionnaire return was very high (> 90%) in both groups at all time points (one, 3, 6 and 12 months) (13). Since this SWAT started more SWATs of unconditional versus conditional trials of monetary incentives for retention have started (14), which are yet to report.…”
Section: Discussionmentioning
confidence: 86%
“…Hardy et al found no evidence that an unconditional incentive of a £10 gift voucher increased response to a postal questionnaire at 1 year in a trial of a maternal intervention at child birth [12]. In contrast, Young et al found that overall an Data shown are n (%) using the number randomised to each group as the denominator unless otherwise specified SD standard deviation, SMS short message service a Host trial stratification variable unconditional incentive of a £5 gift voucher in a lung cancer screening trial in adults aged 50 to 75 years did increase response although the questionnaire return was very high (> 90%) in both groups at all time points (1, 3, 6 and 12 months) [13]. Since this SWAT started more SWATs of unconditional versus conditional trials of monetary incentives for retention have started [14], which are yet to report.…”
Section: Discussionmentioning
confidence: 99%
“…To motivate the participants to complete the whole questionnaire, 5 Amazon vouchers were raffled. Doing so increases the response rate and statistical power in terms of representativity [43,44]. Ultimately 130,685 invitation e-mails were sent which resulted in 2074 completed questionnaires which entered the analysis.…”
Section: Deliberations On Data Collectionmentioning
confidence: 99%